Nonlinear phase switching in microresonators for all-optical computing PICs - Pal, Arghadeep; Ghosh, Alekhya; Zhang, Shuangyou; Hill, Lewis; Bi, Toby; Del'Haye, Pascal (British and Irish Conference on Optics and Photonics, BICOP 2024 in Proceedings British and Irish Conference on Optics and Photonics 2024, 2024)
An optical switch and proposed designs of photonic logic gates exploiting Kerr-effect-mediated phase control of light waves are presented. Our results can be used for integrated all-optical computing and telecom applications.
CRIS-Team Scopus Importer:2025-04-01